National Internationalization Policies in Low- and Mid-Income Countries - de Wit, Hans (International Higher Education, 2020)
In low- and mid-income countries, developing national internationalization policies is mostly a top-down process, and policies are mostly directed from South to North. Mobility is central in most policies and plans. There is a degree of “policy mimicry” in the adoption of many aspects of the Western paradigm, which appears to sustain the dominance of high-income countries. More attention to regional cooperation and a stronger focus on internationalization of the curriculum at home would allow these countries to break through the established paradigm.